EXPORT PERFORMANCE IMPROVEMENT THROUGH MANAGEMENT AND TECHNOLOGY SUPPORT FOR SMEs CRAFT - Nugroho Mardi Wibowo; Yuyun Widiastuti; Siswadi Siswadi (Asian Journal of Innovation and Entrepreneurship, 2017)
Specific targets of this activity are: (i) SMEs can increase turnover; (ii) SMEs can enhance variety of design products; (iii) SMEs have skilled human resources on product design; (iv) SMEs can prepare financial statements; (v) SMEs have a standard quality assurance; (vi) SMEs can improve product quality and speed up the production process; (vii) Obtaining copyrights products. Methods of implementation of this program include: training and assistance with activities such as: the manufacture of machinery and production equipment, supply of equipment, participation in exhibitions, arrangement of storage space and show room, cooperating with other parties as well as the processing of copyright products. The results obtained from these activities, first with the brass foundry furnace and molds made of firebrick resulted in increased speed of production processes as well as fuel efficiency and cost of production for SME-1 "Whisnu". It took only three hours to the cooking process cast brass with a capacity of 120 kg previously take longer that 5 hours. Secondly, Machine Mixer Fiber Materials for Partners "Java Fiber" can shorten the process of mixing the fiber material to be faster, employees are not tired and product quality is getting better and there is no defective products. Fiber material mixing machine can stir 25 kg fiber material for 5 minutes, while the previous manual way takes 1 hour to stir 25 kg fiber. Thirdly, it has been conducted Partners Products Exhibition. Fourth, it generates three new product design by SME-1 "Whisnu" and 4 design new products by SME-2 "Java Fiber". Fifth, the proposed copyright has begun to partner products to the Ministry of Justice and Human Rights. This activity resulted in increased revenue of SMEs 10% per year.